17th AIAA Aviation Technology, Integration, and Operations Conference 2017
DOI: 10.2514/6.2017-3067
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Sizing and Multi-objective Optimization of Aircraft and Subsystem Architectures in Early Design

Abstract: The aerospace industry's current trend towards novel or More Electric architectures results in some unique challenges for designers due to both a scarcity or absence of historical data and a potentially large combinatorial space of possible architectures. These add to the already existing challenges of attempting to optimize an aircraft design in the presence of multiple possible objective functions while avoiding an overly compartmentalized approach. This paper uses the Integrated Subsystem Sizing and Archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…According to the obtained results, shown in figures (5,6), it is obvious that takeoff weight and fuel efficiency coefficient are more sensitive to wing aspect ratio than to its taper ratio. The optimal aspect ratio obtained under the condition of the minimum fuel efficiency coefficient is greater than that under the condition of the minimum takeoff mass, because the fuel efficiency ratio is more sensitive to the aerodynamic characteristics of the aircraft, which increases alongside with aspect ratio.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…According to the obtained results, shown in figures (5,6), it is obvious that takeoff weight and fuel efficiency coefficient are more sensitive to wing aspect ratio than to its taper ratio. The optimal aspect ratio obtained under the condition of the minimum fuel efficiency coefficient is greater than that under the condition of the minimum takeoff mass, because the fuel efficiency ratio is more sensitive to the aerodynamic characteristics of the aircraft, which increases alongside with aspect ratio.…”
Section: Resultsmentioning
confidence: 93%
“…The selection of rational parameters at the preliminary design stage is crucial as it establishes the foundation for subsequent design decisions and ultimately determines the aircraft's overall performance. The academic literatures on this topic focus on several key areas, including aircraft performance, structural design, weight estimation, and optimization methods [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to reduce the size of the combinatorial space, previous studies on subsystem architectures [7,12] considered subsystem electrification bundles or packages using reasoning based on rules with regard to a natural electrification ordering due to technology maturation status. For instance, the predefined strategy for Actuation Function Packages (AFPs) included the Primary Flight Control Actuators (PFCA, that include elevators, ailerons, and rudder), Trimmable Horizontal Stabilizer Actuation (THSA), Spoiler Actuation (SPLA), leading and trailing edge High Lift Device Actuation (HLDA), Nose Wheel Steering System (NWSS), Landing Gear Actuation System (LGAS), Wheel Brake System (WBS), and Thrust Reverser Actuation System (TRAS).…”
Section: Problem Formulationmentioning
confidence: 99%
“…In studies on integrated sizing and multi-objective optimization of aircraft with more-electric architectures by Rajaram et al [12,13], substantially electrified subsystems were found to dominate the Pareto frontier over conventional designs. Their study assumed that all subsystems could be electrified at once.…”
Section: Introductionmentioning
confidence: 99%